Multicriteria Design of Plastic Recycling Based on Quality Information and Environmental Impacts - Nakatani, Jun; Hirao, Masahiko (Journal of industrial ecology, 2011)
Summary In this study, we develop a framework for the multicriteria design of plastic recycling based on quality information and environmental impacts for the purpose of supporting collaborative decision making among consumers, municipalities, and recyclers. The subject of this article is the mechanical recycling of postconsumer polyethylene terephthalate (PET) bottles. We present a “quality conversion matrix,” which links the quality of recycled PET resin to the quality of waste PET bottles and operational conditions, described in terms of the functions of modules constituting the entire recycling process. We estimate the quality of recycled PET resin and simulate the applicability to the intended products as the primary criterion by confirming whether the estimated quality of recycled resin satisfies the quality demands of PET resin users. The amounts of carbon dioxide (CO2) emissions and fossil resource consumption are also estimated as the secondary criteria. An approach to collaborative decision making utilizing mixed‐integer linear programming (MILP) and Monte Carlo simulation is proposed on the premise of different objectives of various stakeholders, where all the feasible optimal solutions for achieving the quality demands are obtained. The quality requirements of waste bottles, along with the CO2 emissions and fossil resource consumption estimated for each solution, contribute to the collaborative multicriteria design of plastic recycling.